1996
DOI: 10.1109/27.533091
|View full text |Cite
|
Sign up to set email alerts
|

A neural-network model of the input/output characteristics of a high-power backward wave oscillator

Abstract: This paper discusses an approach to model the inputloutput characteristics of the Sinus-6 electron beam accelerator-driven backward wave oscillator. Since the Sinus-6 is extremely fast to warrant the inclusion of dynamical effects, and since the sampling interval in the experiment is not fixed, a static continuous neural network model is used to fit the experimental data. Simulation results show that such a simple nonlinear model is sufficient to accurately describe the inputloutput behavior of the Sinus-6-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…From a controls perspective, it turns out that the fast dynamics and changes in the operating characteristics of the BWO render traditional automatic-control methods ineffective. In fact, our results in [7] for the Sinus-6-driven BWO have shown that a static affine model is an accurate representation of its input/output characteristics. A static model is too fast to be controlled in real time while maintaining the sameorder dynamics (and thus, the same bandwidth and speed of response) of the open-loop system.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations
“…From a controls perspective, it turns out that the fast dynamics and changes in the operating characteristics of the BWO render traditional automatic-control methods ineffective. In fact, our results in [7] for the Sinus-6-driven BWO have shown that a static affine model is an accurate representation of its input/output characteristics. A static model is too fast to be controlled in real time while maintaining the sameorder dynamics (and thus, the same bandwidth and speed of response) of the open-loop system.…”
Section: Introductionmentioning
confidence: 78%
“…Note that in the figure, the controller actually contains two parts, one which is based on the known model and is thus fixed and produces , and another denoted by and obtained as the output of the learning controller. In our simulations, the known model is obtained from the identification we performed in [7], which is the neural network fitted to the actual experimental data.…”
Section: A Learning Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…It was this periodic dependence on the output characteristics of our HPM source that we exploited to achieve a "smart tube." A neural network model was developed to describe the input/output characteristics of our HPM source [3]. Furthermore, an ILC algorithm was developed to achieve the control objectives using a minimal number of iterations [4].…”
Section: Introductionmentioning
confidence: 99%